Modeling the Mechanical Response of Tetragonal Lysozyme Crystals - Zamiri, Amir (2010)
In this paper we investigate the mechanical response of tetragonal lysozyme crystals based on existing experimental data and a continuum-based crystal plasticity model. Compression analyses along different crystallographic directions reveal that the mechanical response of lysozyme crystals is highly anisotropic and orientation dependent. While the response is purely elastic along the [110] direction, it is elasto-plastic along the [100] and [2̄ 12] directions. The yield stress and critical resolved shear stress are observed to be sensitive to temperature and the amount of intracrystalline water. An increase in temperature and the amount of intracrystalline water molecules leads to a decrease in the critical resolved shear stress of the slip systems and makes the crystal softer. The analysis presented in this paper may be applied to the study of other protein crystal systems as well as their optimal design for biotechnological applications.